REVIEW: RABIES VIRUS (RABV) DAN PATOGENESISNYA - Maria Aega Gelolodo; Elisabet Tangkonda; Diana A. Wuri; Maxs U. E. Sanam (Partner, 2023)
Rabies, caused by the rabies virus, is a zoonotic infection with a potentially deadly consequence. Both humans and animals are susceptible to this neurotropic virus. The rabies virus is typically present in infected animals' saliva and cerebral tissue, primarily canines, and transmits via bite wounds. Dogs are responsible for most human rabies transmissions, accounting for up to 99% of cases and consequently serving as the predominant contributor to human rabies mortality. This global threat kills approximately 59,000 people a year, with a death rate of nearly 100% in humans and animals. Fever, vomiting, anorexia, and lethargy are some of the non-specific early signs of rabies. Within days, symptoms escalate to deviant behaviour, brain dysfunction, paralysis, convulsions, hypersalivation, respiratory distress, and impaired swallowing. According to its immunological response, it proves that RABV can evade the initial immune defence. Hence, investigating the pathogenesis of RABV infection presents an intriguing study area. Key Words: Rabies, rabies virus, RABV, canine rabies, dog, pathogenesis, immunopathogenesis